PAI Learning Media in The Perspective of Abdullah Nashih Ulwan in The Society Era 5.0 - Mohamad Maulidin Alif Utama (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
In the Society era 5.0, the advancement of technology and knowledge is progressing at a breakneck pace. As a result of this innovation, the way in which society seeks and obtains information, which is no longer restricted to only newspapers, radio, and television, has undergone a paradigm shift. They quickly access the information they need via the internet. One area that has had a significant impact with the development of this technology is education. With the continuous development of the internet, students can use the internet to add knowledge and learning materials. They can look for examples of practice questions to test their abilities. The internet is an essential tool for improving the quality of education. Education is going through a rough patch right now, particularly with regard to Islamic Religious Education Course or PAI after going through the millennial period, which has shown to be difficult to govern in terms of morality and is now also facing a pandemic. The solution that the author offers to deal with this is to use Abdullah Nasih ulwan's thoughts in PAI learning. This research aims to explore Abdullah Nasih Ulwan's thoughts on learning media. This research used a qualitative method, namely a literature review. Data sources were journals and books in the forms of descriptive narratives about Abdullah Nasih Ulwan and Learning Media. As for the results of this research, the media used to deal with today’s situation is to use e-learning and multimedia or digital media such as online applications/platforms, artificial intelligence, augmented reality, gamification, and so on.